Role of SWOT Analysis in Improving Competitiveness in Sambal Special Stall (SS) - Leonardo Budi Hasiholan; Dheasey Amboningtyas (Jurnal Mantik, 2021)
This research was conducted with the aim of finding out what marketing strategies are suitable for WarungSpecial Sambal in 2019. This research uses data collection techniques by means of interviews and observations. The data analysis technique used the Fred R. David concept, namely through the strategy formulation stage, namely the input stage and the matching stage. The input stage uses an internal factory analysis summary (IFAS) matrix and an external factory analysis summary (EFAS) matrix. And the last stage is to use the SWOT Matrix and internal - external (IE). Based on the results of IFAS and EFAS, it can be seen that the total value for IFAS is 3.145 while the EFAS result is 2.778. use strengths to take advantage of opportunities, take advantage of opportunities to overcome weaknesses, use strengths to avoid threats, and minimize weaknesses and avoid threats. In the external internal matrix (IE), it is known that CV Patlapan Mandiri Primafood Semarang is in a business growth phase. This result is evidenced in the internal and external SWOT matrix which shows the state of the company is in cell 1. The right strategy applied to CV Patlapan Mandiri Primafood at this time is to SO strategy (Strength Opportunities)